2015
DOI: 10.1039/c5an01471a
|View full text |Cite
|
Sign up to set email alerts
|

Rapid and efficient pesticide detection via cyclodextrin-promoted energy transfer

Abstract: Cyclodextrins facilitate non-covalent fluorescence energy transfer from a variety of pesticides to high quantum-yield fluorophores, resulting in a rapid, sensitive detection scheme for these compounds with detection limits as low as two micromolar.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

7
1

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 49 publications
1
17
0
Order By: Relevance
“…We demonstrated that this toxicant detection system operates in a broad range of environments, including plasma, 32 breast milk, 33 and urine, 34 as well as in extracts collected in the aftermath of the 2010 Deepwater Horizon oil spill. 35 Although our previous work detected polycyclic aromatic hydrocarbons, 36 polychlorinated biphenyls, 37 aromatic amines, pesticides, 38 aliphatic alcohols, and fuel spill components, we have not used cyclodextrin systems for the detection of BPA and BPA derivatives to date.…”
Section: Fig 1 Schematic Of Cyclodextrin-promoted (A) Energy Transfementioning
confidence: 96%
“…We demonstrated that this toxicant detection system operates in a broad range of environments, including plasma, 32 breast milk, 33 and urine, 34 as well as in extracts collected in the aftermath of the 2010 Deepwater Horizon oil spill. 35 Although our previous work detected polycyclic aromatic hydrocarbons, 36 polychlorinated biphenyls, 37 aromatic amines, pesticides, 38 aliphatic alcohols, and fuel spill components, we have not used cyclodextrin systems for the detection of BPA and BPA derivatives to date.…”
Section: Fig 1 Schematic Of Cyclodextrin-promoted (A) Energy Transfementioning
confidence: 96%
“…Such complexes, in turn, effectively limit interactions between the analyte and fluorophore, resulting in a fluorophore emission that is relatively unaffected by the presence of the analyte. For the remainder of the studies, we chose 10 mM cyclodextrin solutions based on previously reported results showing high performance of 10 mM cyclodextrin in promoting energy transfer [19][20][21]23].…”
Section: Concentration-dependent Energy-transfer Experimentsmentioning
confidence: 99%
“…In cases of non-photophysically active analytes, cyclodextrin promotes interactions between the analyte and the fluorophore, resulting in analyte-specific fluorescence modulation [16,17]. We have reported the detection of numerous classes of analytes using these chemosensors, including polycyclic aromatic hydrocarbons (PAHs) [18,19], polychlorinated biphenyls (PCBs) [20], pesticides [21], and aliphatic alcohols [22], as well as the ability of such systems to operate in plasma [23], urine [24], and breast milk [25].…”
Section: Introductionmentioning
confidence: 99%
“…Aromatic organochlorine pesticides have already been detected by our group using cyclodextrinpromoted energy transfer to fluorophores 6-8, 27 and a variety of aliphatic alcohols have been detected via cyclodextrinpromoted fluorescence modulation (Table 6). 28 In general, the limits of detection for the alkanols are higher than those of the aliphatic organochlorine pesticides, highlighting a lower degree of sensitivity for these other analytes.…”
Section: Mechanism Of Differentiationmentioning
confidence: 99%